2021
DOI: 10.3390/nano11010117
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Double- and Single-Clamped CuO Nanowire Based Nanoelectromechanical Switches

Abstract: Electrostatically actuated nanoelectromechanical (NEM) switches hold promise for operation with sharply defined ON/OFF states, high ON/OFF current ratio, low OFF state power consumption, and a compact design. The present challenge for the development of nanoelectromechanical system (NEMS) technology is fabrication of single nanowire based NEM switches. In this work, we demonstrate the first application of CuO nanowires as NEM switch active elements. We develop bottom-up and top-down approaches for NEM switch f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…For the fabrication of NEM devices, longer nanowires with diameters below 100 nm are preferable, because they provide lower switch-on voltages and lower adhesion in the contact [41]. The best characteristics for application in NEMS are demonstrated for nanowires synthesized by simple oxidation of Cu in dry air (mean diameter appr.…”
Section: Mechanical Characterizationmentioning
confidence: 99%
“…For the fabrication of NEM devices, longer nanowires with diameters below 100 nm are preferable, because they provide lower switch-on voltages and lower adhesion in the contact [41]. The best characteristics for application in NEMS are demonstrated for nanowires synthesized by simple oxidation of Cu in dry air (mean diameter appr.…”
Section: Mechanical Characterizationmentioning
confidence: 99%
“…178 Currently, the development of new technology based on high-performance nanoelectromechanical systems (NEMS) is limited by the problems associated with the synthesis of NEM switches based on single nanowires. A successful application of CuO nanowires as a NEM switch element was recently reported by Jasulaneca et al 179 Moreover, the anodized copper foams obtained by Abd-Elnaiem et al have been to be an efficient material for enhancing the efficiency of organic dye decomposition. 180 A number of experiments carried out to develop a method for the highly-controllable synthesis of nanostructures includes a stage achieves metal nanoparticle deposition.…”
Section: Innovations In Cuo Nanowire-based Metamaterials For Energy A...mentioning
confidence: 98%
“…The gap is 300 nm, and the pull-in voltage is 70 V. As the width is reduced to 200 nm and the gap is reduced to 100 nm, the pull-in voltage is reduced to 5 V. The switching current ratio is greater than 10 6 , and the number of life cycles is greater than 10 5 . Jasulaneca et al [ 8 ] made a CuO NWs switch, 3 µm long, 80 nm in diameter, and 120 nm in the gap, with a pull-in voltage of 12.5 V. Feng et al [ 40 ] prepared SiC nanowire NEM switches using bottom-up techniques. The pull-in voltage ranges from one to several volts and the response time is below microseconds with a switching ratio of about 10 3 .…”
Section: Reviewmentioning
confidence: 99%
“…Extensive research has shown that modeling the bending of the flexible devices is only limited to the mechanical behavior of the flexible interconnect lines, and hardly involves the structure of the flexible devices. Nanoelectromechanical (NEM) switches made of carbon nanotubes (CNTs) [ 2 4 ], graphene (GR) [ 5 7 ], nanowires (NWs) [ 8 10 ], and other flexible materials are the most basic devices for a variety of component and system level applications, such as low-loss switches, phase shifts, and relays.…”
Section: Introductionmentioning
confidence: 99%